Identity & the globalization of Nusantara - Suyatno, Ladiqi; Mohd Afandi, Salleh; Baiq, Wardhani; Vinsensio, Dugis; Ismail Suardi, Wekk (2019)
t. The phenomenon of globalization in Nusantara actually was happened for long time ago. There is international trade between Nusantara and some countries in Asia and Europe. The meetings between traders in that era reflected the encounter of different civilizations as well as, that was able to transcend geographical and cultural boundaries. This paper would like to seek for an explanation about the phenomenon of globalization which Nusantara is taking a pivotal role in international trade. There are a lot of goods traded in that time, such as spices as a mainstay product. Important to explore the glory of Nusantara since, regarding modern era, identity must be supported by strong root history through shared memory and experience. Nusantara must be reinvented as a strong provision to strengthen national identity which is increasingly threatened by modernization.